BIO-DRYING AS PRE-TREATMENT REFUSE DERIVED FUEL (RDF) GENERATION FOR COMBUSTIBLE WASTE TREATMENT - Latifah, Mauliddani
The increase of energy consumption and waste generation are two emerged effects of economic and population growths. Developing alternative energy by waste utilization using waste to energy concept is now researched and developed. Refuse derived fuel (RDF), being one of the alternative energy in solid waste treatment derived from solid waste separating processes among combustible and non-combustible waste fractions. There are standard criteria of RDF such as low water content (10-25%) and LHV is around >3487,15-5995,03 kcal/kg. Unfortunately, municipal waste characteristic is typically high water content. Food waste dominates the high water content in MSW. In order to be appropriate for the RDF standard, it is needed a pre-treatment of selected MSW using an optimum drying. The objective of this research conducts a pre-treatment for selected combustible waste using drying methods variations. This research used a combustible waste from Cibeunying Disposal and Bengkok Canteen of ITB. It also used two reactors with 60 liters capacity of volume and 10 kg of weight. Convective drying reactor comprised a 500C heater and a sensor within. The bio-drying was conducted in 14 days with two conditions, hydrolytic-aerobic and aerobic. The convective drying was in 5 hours. pH, temperature, Lower Heating Value (LHV) (kcal/kg), water content (% ww), volatile content (% dw), lignocellulose content (lignin, cellulose and hemicellulose) were analyzed. Initial characteristic of sample has high water content around 54-55 % (w/w) and 1500-2300 kcal/kg of LHV. Temperature evolution occurred on every process of reactors. Peak of temperature is always reached at aerobic phase. Peak of temperature of aerobic process occurred in the first days of the process. While in hydrolytic-aerobic process occurred after it is settled into aerobic phase. In the end of v treatment, total water content reduction of aerobic and hydrolytic-aerobic were 20.53% and 31.45%, respectively. Total material degradation of aerobic and hydrolytic-aerobic were 21.83% and 26.48%, respectively. All products are not fulfilling the RDF standard, yet. Therefore, all processes are more suitable being a pre-treatment of RDF generation.